In vitro IL-15-activated human naïve CD8+ T cells down-modulate the CD8β chain and become CD8αα T cells - Esgalhado, André J.; Reste-Ferreira, Débora; Weinhold, Sandra; Uhrberg, Markus; Cardoso, Elsa M.; Arosa, Fernando A. (Frontiers in Immunology, 2024)
Antigen-driven human effector-memory CD8+ T cells expressing low levels of the CD8β chain have been previously described. However, little is known on a possible antigen-independent trigger. We have examined the impact that IL-15 has on the expression of CD8β on purified human naïve CD8+ T cells after CFSE labeling and culture with IL-15. As expected, IL-15 induced naïve CD8+ T cells to proliferate and differentiate. Remarkably, the process was associated with a cell-cycle dependent down-modulation of CD8β from the cell surface, leading to the generation of CD8αβlow and CD8αβ− (i.e., CD8αα) T cells. In contrast, expression of the CD8α chain remained steady or even increased. Neither IL-2 nor IL-7 reproduced the effect of IL-15. Determination of mRNA levels for CD8α and CD8β isoforms by qPCR revealed that IL-15 promoted a significant decrease in mRNA levels of the CD8β M-4 isoform, while levels of the M-1/M-2 isoforms and of CD8α increased. Noteworthy, CD8+ T cell blasts obtained after culture of CD8+ T cells with IL-15 showed a cell-cycle dependent increase in the level of the tyrosine kinase Lck, when compared to CD8+ T cells at day 0. This study has shown for the first time that IL-15 generates CD8αα+αβlow and CD8αα+αβ− T cells containing high levels of Lck, suggesting that they may be endowed with unique functional features.